The Federated States of Micronesia's Engagement with the Outside World Control, Self-Preservation and Continuity - Puas, Gonzaga (Pacific Series, 2021)
This study addresses the neglected history of the people of the Federated States of Micronesia's (FSM) engagement with the outside world. Situated in the northwest Pacific, FSM's strategic location has led to four colonial rulers. Histories of FSM to date have been largely written by sympathetic outsiders. Indigenous perspectives of FSM history have been largely absent from the main corpus of historical literature. A new generation of Micronesian scholars are starting to write their own history from Micronesian perspectives and using Micronesian forms of history. This book argues that Micronesians have been dealing successfully with the outside world throughout the colonial era in ways colonial authorities were often unaware of. This argument is sustained by examination of oral histories, secondary sources, interviews, field research and the personal experience of a person raised in the Mortlock Islands of Chuuk State. It reconstructs how Micronesian internal processes for social stability and mutual support endured, rather than succumbing to the different waves of colonisation. This study argues that colonisation did not destroy Micronesian cultures and identities, but that Micronesians recontextualised the changing conditions to suit their own circumstances. Their success rested on the indigenous doctrines of adaptation, assimilation and accommodation deeply rooted in the kinship doctrine of eaea fengen (sharing) and alilis fengen (assisting each other). These values pervade the Constitution of the FSM, which formally defines the modern identity of its indigenous peoples, reasserting and perpetuating Micronesian values and future continuity.